Research status and development trends of probiotics in clinical applications - Li, Yang; Yao, Yucheng; Zhang, Zan; Gan, Yongqi (Frontiers in Nutrition, 2025)
Background:In recent years, the potential role of probiotics in modulating gut microbiota, enhancing immune function and improving metabolic diseases has become a highly field in biomedical and clinical research. The rapid increase in global probiotic clinical trials necessitates a systematic evaluation of current research status, developmental trends, and collaborative networks in this field.PurposeThis study employs bibliometric analysis to comprehensively evaluate research progress and hotspots in clinical applications of probiotics.MethodA systematic search was performed in the Web of Science database to collect articles and reviews regarding the clinical application of probiotics between 2000 and 2025. The retrieved records were analyzed using Microsoft Office Excel, Cite Space and VOS viewers.ResultDuring the period from 2000 to 2025, we retrieved a total of 3,674 papers related to the clinical application of probiotics, and the number of papers is showing a continuous growth trend. The research was mainly focused on North America, Western Europe, and East Asia, with the United States leading the way with 714 papers, high impact (H-index 107, total citations 44,833), and top institutions (Harvard Univ). Nutrition and microbiology are the main academic fields. The current research hotspots and development directions focus on the application of probiotics in diseases such as “inflammation”, “obesity”, “insulin resistance”, “depression”, “hyperlipidemia”, and “cancer”.ConclusionThis study represents the first application of bibliometric methods to systematically visualize and analyze research progress in the field of probiotic clinical applications, identifying key research trends and frontiers. The findings offer valuable insights for researchers at various career stages, particularly those new to the field, enabling them to identify critical developments and serving as a foundational reference for future clinical applications of probiotics.